Efektivitas Penerapan Metode Bermain Peran Makro terhadap Perkembangan Bahasa Lisan Anak di Taman Kanak-kanak Darul Falah Kota Padang - Putri, Maidita; Rakimahwati, Rakimahwati; Zulminiati, Zulminiati (Journal of Studies in Early Childhood Education (J-SECE), 2018)
This study aims to find out how  effective of the application of macro roles playing methods for the development of the oral language of children in the kindergarten of Darul Falah Padang city. This research uses quantitative approach with quasi-experiment research type. The study population is students in the kindergarten of Darul Falah Padang city and the sampling technique is purposive sampling. The data collection technique uses a test in the form of a statement of 4 statement items. Assessment techniques in this study use rating scale and the data is processed by difference test (t-test) and the effect size test with Cohenâs formula d to find out the magnitude of the influence.Based on the calculation of the t-test (t-test) obtained tcount of 3,1645 while the ttable is a 2,10092 at the real level ?=0,05 so that tcount> ttable and the effect size tets of the t-test is obtained for 1,488. Thus it can be concluded that macro roles playing methods are effective against the development of childrenâs oral language in the kindergarten of Darul Falah Padang city.